Constructing College-Level Diversity, Equity, and Inclusion (DEI) Minors—Moving from Performative to Transformative DEI - Gibbs, Carole; Achebe, Nwando; Johnson, Brian; Nwaiche, Chioma; Velez Ortiz, Daniel (Radical Teacher, 2023)
In a period of growing support as well as hostility toward, diversity, equity and inclusion (DEI) in the United States, we developed two college-level DEI minors. We grounded each minor in critical pedagogy, a broad theoretical and philosophical perspective on the purpose and process of education that encapsulates a variety of practices and methods. The goal was to move beyond performative DEI by collaborating with students to develop the necessary tools to become engaged and self-managed citizens both nationally and globally. As such, we embedded dialogue, self-reflection, diverse knowledge networks and sources, and critical frameworks into the minors, as we sought to balance developing critical awareness with working toward change. In the following paper, we describe these basic elements of critical pedagogy to transformative DEI and link them to the processes of constructing and ultimately delivering the minors. Key examples are provided to demonstrate the implementation of these elements in our work. We conclude with our reflections on how this experience may inform similar efforts.